On the nature of Tycho Brahe’s supernova - Ruiz–Lapuente, Pilar (Frontiers in Astronomy and Space Sciences, 2023)
At the 450 yr anniversary of its observation, the supernova named after Tycho Brahe, SN 1572, can be explained in the terms used nowadays to characterize Type Ia supernovae (SNe Ia). By assembling the records of the observations made in 1572--74 and evaluating their uncertainties, it is possible to recover the light curve and the color evolution of this supernova. It is found that, within the SNe Ia family, the event should have been a SN Ia with a normal rate of decline. Concerning the color evolution of SNe Ia, the most recently recovered records reaffirm previous findings of its being a normal SN Ia. The abundance studies from X--ray spectroscopy of the whole remnant point to a nuclear burning of the kind of a delayed detonation explosion of a Chandrasekhar--mass white dwarf. A tentative single degenerate path to explosion was suggested from the exploration of the stars in the field in SN 1572. Though, the origin in a double degenerate is being considered as well. Tycho Brahe's supernova, being the first supernova studied by astronomers, is still the subject of very intensive debates nowadays.